Neuronal oscillations: A physiological correlate for targeting mitochondrial dysfunction in neurodegenerative diseases?. (March 2016) - Chan, Felix; Lax, Nichola Z.; Davies, Ceri H.; Turnbull, Douglass M.; Cunningham, Mark O.
Abstract: Increasingly in the realm of neurological disorders, particularly those involving neurodegeneration, mitochondrial dysfunction is emerging at the core of their pathogenic processes. Most of these diseases still lack effective treatment and are hampered by a shortfall in the development of novel medicines. Clearly new targets that translate well to the clinic are required. Physiological parameters in the form of neuronal network activity are increasingly being used as a therapeutic screening approach in drug development and disorders with mitochondrial dysfunction generally display neuronal network activity disturbance. However research directly linking the disturbances in neuronal network activity with mitochondrial dysfunction is only just starting to emerge. This review will summarize the breadth of knowledge linking neuronal network activity to mitochondrial dysfunction in neurodegenerative diseases and suggest potential avenues for exploration in respect to future drug development. Highlights: Mitochondrial dysfunction and neuronal oscillations are linked in neurodegeneration. Neuronal oscillations correlate with mitochondrial dysfunction in neurodegeneration. Neuronal oscillations should guide drug development in neurodegenerative disease.